The role of the committee in improving the education quality of madrasa - Gunawan, Agus; Uyuni, Yuyun Rohmatul (ATTARBIYAH: Journal of Islamic Culture and Education, 2022)
Educational management is very important as a modern culture that prepares quality human resources. The formation of madrasa committees in each madrasah unit provides the impetus for better management, even though the madrasa committee is still not functioning optimally. The madrasa committee management factor is the government's focus on maintaining the quality of education as stipulated in the Regulation of the Minister of Religion Number 16 of 2020. The madrasa committee becomes independent, professional, and modern to maintain and improve the quality of education. This study aimed to analyze the role of madrasa committee management on the quality of education. The research uses quantitative methods, and the object of research is State Madrasah in Banten Province. The magnitude of the role of madrasah committee management on the quality of education is 82.4%, indicating that madrasah management can maintain the quality of education specified. In contrast, madrasah policy planning and budgeting are dominant in madrasah committee management. The implication is that the madrasah's efforts to support the maximum implementation of the duties and functions of the madrasah committee and training efforts for the madrasah committee.